BIOSINTESIS LAPISAN TIPIS ZnO MENGGUNAKAN EKSTRAK TEMU KUNCI (BOESENBERGIA PANDURATA) DENGAN METODE SPIN COATING: VARIASI WAKTU PERTUMBUHAN - Nuri Amalia; Emsal Yanuar; Lalu Suhaimi (Hexagon, 2023)
Properties such as photocatalytic, electrical, optical, and antibacterial. This paper presents research on the biosynthesis of ZnO nanoparticles using fingerroot extract with the spin coating method at various growth times. The process begins with preparing a seed solution with a concentration of 0.5M at a temperature of 60? at a speed of 1000 rpm for 60 minute. Furthermore, the preparation of seed layers with the spin coating technique. ZnO nanostructured thin films were grown with variations 3 hours and 4 hours. The results of SEM analysis showed the morphology of ZnO was spherical and agglomeration occurred in each variation. The average grain size of ZnO at 3 hours of growth time was 88.61 nm and 58.23 nm at 4 hours. The results of the XRD pattern analysis showed that each of the ZnO samples had a high crystallinity with a hexagonal shape, with. Crystal size at 3 hours of growth is 25.8 nm and 4 hours is 34.4 nm. Energy gap values at 3 hours of growth are 3.40 eV and 4 hours are 3.85 eV. The absorbance value was relatively high in the 3 hour treatment with a wavelength of 215 and in the 4 hour treatment with a wavelength of 245nm.